Differential Effector Function of Tissue-Specific Natural Killer Cells against Lung Tumors - Zerick Terrell Dunbar; Salvador González-Ochoa; Thanigaivelan Kanagasabai; Alla Ivanova; Anil Shanker (Journal of Innate Immunity)
Introduction: Natural killer (NK) cells are innate lymphoid cells capable of directly killing target cells while modulating immune effector responses. Despite their multifunctional capacities, a limited understanding of their plasticity and heterogeneity has impeded progress in developing effective NK cell-based cancer therapies. In this study, we investigated NK cell tissue heterogeneity in relation to their phenotype and effector functions against lung tumors. Methods: Using hanging drop tumor spheroid and subcutaneously established LL/2 (LLC1) lung tumor models, we examined NK cell receptor diversity and its correlation with tissue-specific cytotoxicity through multiparametric flow cytometry, fluorescence imaging, and cytotoxicity assays. Results: We identified distinct patterns of cell surface receptors expression on tissue-specific NK cells that are crucial for antitumor activity. Linear regression mathematical analyses further revealed significant positive correlations between activation-associated cell surface receptors and cytotoxic capacity in NK cells from tissues such as the liver and bone marrow. Conclusion: These findings underscore the differential effector capacities of NK cells from distinct tissues, even prior to exposure to LL/2 tumor cells. This highlights the significance of tissue-specific NK cell heterogeneity and its impact on their antitumor cytotoxicity. Recognizing these distinct tissue-specific receptor expression patterns will be instrumental in developing more efficacious NK cell-based cancer treatments.